Alphavirus Restriction by IFITM Proteins. (24th June 2016) - Weston, Stuart; Czieso, Stephanie; White, Ian J.; Smith, Sarah E.; Wash, Rachael S.; Diaz‐Soria, Carmen; Kellam, Paul; Marsh, Mark
Abstract : Interferon inducible transmembrane proteins (IFITMs) are broad‐spectrum antiviral factors. In cell culture the entry of many enveloped viruses, including orthomyxo‐, flavi‐, and filoviruses, is inhibited by IFITMs, though the mechanism(s) involved remain unclear and may vary between viruses. We demonstrate that Sindbis and Semliki Forest virus (SFV), which both use endocytosis and acid‐induced membrane fusion in early endosomes to infect cells, are restricted by the early endosomal IFITM3. The late endosomal IFITM2 is less restrictive and the plasma membrane IFITM1 does not inhibit normal infection by either virus. IFITM3 inhibits release of the SFV capsid into the cytosol, without inhibiting binding, internalization, trafficking to endosomes or low pH‐induced conformational changes in the envelope glycoprotein. Infection by SFV fusion at the cell surface was inhibited by IFITM1, but was equally inhibited by IFITM3. Furthermore, an IFITM3 mutant (Y20A) that is localized to the plasma membrane inhibited infection by cell surface fusion more potently than IFITM1. Together, these results indicate that IFITMs, in particular IFITM3, can restrict alphavirus infection by inhibiting viral fusion with cellular membranes. That IFITM3 can restrict SFV infection by fusion at the cell surface equivalently to IFITM1 suggests that IFITM3 has greater antiviral potency against SFV. Abstract : IFITM3 can inhibit cellular infection by two alphaviruses, Sindbis and Semliki Forest virus (SFV). IFITM2 has lower antiviral activity, and IFITM1 does not restrict either virus through the endocytic route of infection. IFITM3 does not inhibit SFV binding, internalization into cells, trafficking to endosomes or low pH‐induced conformational changes in the E1 fusion protein. However, the viral capsid is not released into the cytosol in IFITM3 expressing cells.